The relationship between eruptive activity, flank collapse, and sea level at volcanic islands: A long‐term (>1 Ma) record offshore Montserrat, Lesser Antilles. (16th July 2016) - Coussens, Maya; Wall‐Palmer, Deborah; Talling, Peter. J.; Watt, Sebastian. F. L.; Cassidy, Michael; Jutzeler, Martin; Clare, Michael A.; Hunt, James. E.; Manga, Michael; Gernon, Thomas. M.; Palmer, Martin. R.; Hatter, Stuart. J.; et al.
Abstract: Hole U1395B, drilled southeast of Montserrat during Integrated Ocean Drilling Program Expedition 340, provides a long (>1 Ma) and detailed record of eruptive and mass‐wasting events (>130 discrete events). This record can be used to explore the temporal evolution in volcanic activity and landslides at an arc volcano. Analysis of tephra fall and volcaniclastic turbidite deposits in the drill cores reveals three heightened periods of volcanic activity on the island of Montserrat (∼930 to ∼900 ka, ∼810 to ∼760 ka, and ∼190 to ∼120 ka) that coincide with periods of increased volcano instability and mass‐wasting. The youngest of these periods marks the peak in activity at the Soufrière Hills volcano. The largest flank collapse of this volcano (∼130 ka) occurred toward the end of this period, and two younger landslides also occurred during a period of relatively elevated volcanism. These three landslides represent the only large (>0.3 km 3 ) flank collapses of the Soufrière Hills edifice, and their timing also coincides with periods of rapid sea level rise (>5 m/ka). Available age data from other island arc volcanoes suggest a general correlation between the timing of large landslides and periods of rapid sea level rise, but this is not observed for volcanoes in intraplate ocean settings. We thus infer that rapid sea level rise may modulate the timing of collapse at island arc volcanoes, but not in larger ocean‐island settings. Key Points: Heightened volcanic activity on Montserrat at 120–190, 760–810, and 900–930 ka Large landslides coincide with rapid sea level rise at island arc volcanoes